Grammatical Observations on Euripides' Bacchae - Rijksbaron, Albert, (Amsterdam Studies in Classical Philology ;, 1990)
Rijksbaron, A. Grammatical Observations on Euripides' Bacchae. 1990 'No other play of Euripides has been so much discussed as the Bacchae; very few have been the subject of such exact and careful study on the linguistic side'. Thus opens the preface to the first edition of Dodds' commentary. One might subscribe to these words nowadays even more readily than at their original date of publication (1944), if only because Dodds himself has added considerably to our understanding of the play. Nevertheless, as Dr Rijksbaron argues in this commentary-like book, the linguistic side may be due for a reappraisal. This reappraisal does not so much consist in applying the latest insights of general and Greek linguistics, but rather in making use of the impressive grammatical apparatus which is at the disposal of classical philologists, but whose value is not always fully acknowledged, as the commentaries on the Bacchae show. ASCP 1 (1990), 227 p. Cloth. - 32.00 EURO, ISBN: 9050630413